Factors associated with hospitalizations for conditions sensitive to primary care in adult and elderly patients in Brazil: integrative literature review (Research, Society and Development, 2023)
Objective: To identify and analyze scientific publications about the main factors that lead to Hospitalizations for Conditions Sensitive to Primary Care (ACSC) in adult and elderly patients. Method: This is an integrative literature review, whose data search was performed in the databases: PUBMED, LILACS, MENDELEY and SCIELO using the descriptors “Hospitalizations for ambulatory care sensitive conditions”, “Brazil”. Results and Discussion: A total of 221 studies were identified in the aforementioned databases. With 59 in PubMed, 29 in Scielo, 60 in Lilacs and 73 in Mendeley. After inclusion and exclusion criteria, the final sample consisted of 10 articles. Regarding the type of study method, ecological studies prevailed. As for the main factors associated with ACSC, the expansion of APS; the technical knowledge of the Health Team; low per capita income; population education; the improvement of diagnostic methods and clinical follow-up; the low sanitary infrastructure; and age group were the most prevalent. Conclusion: It is concluded that the reduction of ICSAP depends on the improvement of the Brazilian public health system, especially primary care, and also on the quality of life of the population, with emphasis on population groups in a state of social vulnerability.